Tantangan Revolusi Industri 4.0. dengan Konsep Pengembangan Life Skill di Lembaga Pendidikan - Mohammad Khusnul Hamdani (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2021)
A life cycle that undergoes vertical turnover requires a coherent concept. The various problems and solutions offered in life now depend on everyone who takes it. Not a few high schoolers who just graduated do not have life skills. Life skills are needed to address various problems, be it work, home, or independence. With the era of industrial rovollusi generation Indonesia needs to print a generation that is independent and free from dependence. Not a few unemployed in Indonesia have an impact on the economy. Education at least has a role by equipping students in addressing life in various aspects. Educators are taking on more roles to make students ready for the industrial revolution 4.0. Not a few children who do not have a minimal life skill so get lost in the negative and destructive.